ISDN2014_0070: REMOVED: In vivo examination of the relationship between estrogen receptors and microtubule dynamic: A new hypothesis about neuronal degeneration. Issue 47 (5th November 2015) - Karamese, Murat; Aksak Karamese, Selina; Karakus, Emre; Gundogdu, Ozge B.; Unal, Bunyami
Abstract : This article has been removed: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our‐business/policies/article‐withdrawal ) This meeting abstract has been removed by the Publisher. Due to an administrative error, abstracts that were not presented at the ISDN 2014 meeting were inadvertently published in the meeting's abstract supplement. The Publisher apologizes to the authors and readers for this error.